Answer:
y1 = -5
y2 = -1
y3 = 5
y4 = 9
Explanation:
The equation of the table is
y = 2x - 5
The table is
→ x → y
→ 0 → y1
→ 2 → y2
→ 5 → y3
→ 7 → y4
To complete the table by finding the values of y substitute every x in the equation by its value to find the corresponding y
∵ y = 2x - 5
∵ x = 0
→ Substitute x by 0
∴ y1 = 2(0) - 5
∴ y1 = 0 - 5
∴ y1 = -5
∵ y = 2x - 5
∵ x = 2
→ Substitute x by 2
∴ y2 = 2(2) - 5
∴ y2 = 4 - 5
∴ y2 = -1
∵ y = 2x - 5
∵ x = 5
→ Substitute x by 5
∴ y3 = 2(5) - 5
∴ y3 = 10 - 5
∴ y3 = 5
∵ y = 2x - 5
∵ x = 7
→ Substitute x by 7
∴ y4 = 2(7) - 5
∴ y4 = 14 - 5
∴ y4 = 9